1978
DOI: 10.1073/pnas.75.11.5631
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of DNA sequence adjacent to human beta-globin structural gene: relationship to sickle mutation.

Abstract: Restriction endonuclease mapping of the human globin genes revealed a genetic variation in a Hpa I recognition site about 5000 nucleotides from the 3' end of the P-glo in structural gene. Instead of a normal 7.6-kilobase (kb) fragment which contains the globin structural gene, 7.0-kb and 13.0-kb variants were detecte. Both variants were found in eople of African origin and were not detected in Asians or Caucasians. The 13.0-kb variant is frequently associated with the sickle hemoglobin mutation and may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
180
0
13

Year Published

1980
1980
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 702 publications
(194 citation statements)
references
References 20 publications
1
180
0
13
Order By: Relevance
“…The emergence of assays to directly analyze DNA sequence variation enabled investigators to identify mutations at the molecular level and explore their mechanisms of action[18]. The first DNA-based assays screened for mutations at restriction sites that resulted in a restriction fragment length polymorphism (RFLP)[19]. The development of nucleotide sequencing methods subsequently permitted the analysis of small sections of genomic DNA for allelic variants after cloning[20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of assays to directly analyze DNA sequence variation enabled investigators to identify mutations at the molecular level and explore their mechanisms of action[18]. The first DNA-based assays screened for mutations at restriction sites that resulted in a restriction fragment length polymorphism (RFLP)[19]. The development of nucleotide sequencing methods subsequently permitted the analysis of small sections of genomic DNA for allelic variants after cloning[20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…They are caused by mutated or reduced expression of the adult-stage beta-globin gene (1,2) and manifested when gene expression in the betaglobin locus sequentially switches from fetal to adult types (3) around the time of birth. It is predicted that maintaining fetal hemoglobin (HbF) at levels above 30% in circulating red cells should prevent the manifestation of most sickle-cell disease complications (4).…”
mentioning
confidence: 99%
“…In 1978, Kan and Dozy reported that many Blacks suffering from sickle cell anaemia lacked a HpaI site at the 3' flanking region of their ,B-globin gene (Kan & Dozy, 1978). The linkage disequilibrium between a restriction fragment length polymorphism (RFLP) and the sickle cell mutation in this ethnic group has led to the more extensive studies of DNA polymorphisms in the ,B-globin cluster.…”
Section: Vol 226mentioning
confidence: 99%